Gendering and Constructing Violence in Ellen McLaughlin’s Ajax in Iraq - Barrak , Thamir Saad; Salih , Elaff Ghanim (Dirasat: Human and Social Sciences, 2023)
Objective: This study examines the reality of women soldiers’ violence in Ellen McLaughlin’s Ajax in Iraq and argues that women soldiers—like men—can be perpetrators of violence. Methods: The study is conducted in light of Judith Butler’s concept of performativity as theorized in her book Gender Trouble: Feminism and the Subversion of Identity (1990). In relation to Butler’s theorization, which assumes that gender is a social construct, the characters’ violent acts and behaviors are analyzed in order to explore men and women soldiers’ violence. Results: The study shows that the behaviors of the female soldier in the play go beyond the binary narrative of gender performance as well as the social construction of violence. This portrayal of violent acts suggests that acts of violence are de-gendered and that both men and women can be both victims and perpetrators of violence. Conclusions: The study concludes that acts of violence of military women are re-gendered and de-constructed through women’s performance in the play. It also shows that women soldiers’ behaviors are affected by women’s cultural and social environments, a situation which indicates that the binary system of understanding violence fuels inequality between the genders.